Simultaneous Determination of 32 Pyrrolizidine Alkaloids in Two Traditional Chinese Medicine Preparations by UPLC-MS/MS - Shi Cheng; Wei Sun; Xiaoning Zhao; Ping Wang; Wensheng Zhang; Shunnan Zhang; Xiangwei Chang; Zhengliang Ye (Journal of Analytical Methods in Chemistry)
Pyrrolizidine alkaloids (PAs) constitute a class of phytotoxin which demonstrates strong hepatotoxicity. In China, many plants containing PAs are used as traditional medicines or medicinal preparations, which could harm human health and safety. Xiaoyao Tablet (XYT) is an antidepressant drug registered in the European Union (EU), Compound Danshen Dropping Pills (CDDP) is a commonly used drug for coronary heart disease, and phase III clinical study is ongoing in the United States. The purpose of this study is to provide data to support the use of Chinese medicine preparations internationally and to establish analytical methods for 32 PAs in XYT and CDDP. The extraction parameters that were optimized include solid-phase extraction (SPE) cartridge, extraction method, and extraction solvent. Then ultra-performance liquid chromatography coupled with triple-quadrupole linear ion-traptandem mass spectrometry (UPLC-MS/MS) was developed to effectively and efficiently quantify the 32 PAs of the XYT and CDDP. The analytical methods for XYT and CDDP were verified respectively. For XYT, the analytical method for 32 PAs was linear, and the correlation coefficient r was greater than 0.994; the recovery (REC%) at 10–2000 μg/kg was 73.3%–118.5%, and the relative standard deviation (RSD%) was 2.1%–15.4%. The CDDP REC% was 71.8%–112.0%, and the RSD% was 2.0%–17.1%. This study provides technical and data support for the registration of Chinese patented medicines in the EU, controls quality and ensures safety, and is committed to the internationalization and standardization of Chinese patented medicines.